Cannabinoids for Agitation in Alzheimer’s Disease - Outen, John D. (Am J Geriatr Psychiatry, 2021)
Agitation is a common neuropsychiatric symptom of Alzheimer’s disease (AD) that greatly impacts quality of life and amplifies caregiver burden. Agitation in AD may be associated with volume loss in the anterior cingulate cortex, posterior cingulate cortex, insula, amygdala, and frontal cortex, as well as with degeneration of monoaminergic neurotransmission, disrupted circadian rhythms, and frailty. Current pharmacological options have troubling safety concerns and only modest efficacy. There is increasing interest in cannabinoids as promising agents due to pre-clinical and early clinical research that suggest cannabinoids can elicit anxiolytic, antidepressant, and/or anti-inflammatory effects. Cannabinoids may relieve agitation by regulating neurotransmitters, improving comorbidities and circadian rhythms, and increasing cerebral circulation. Here we discuss the possible contributory mechanisms for agitation in AD and the therapeutic relevance of cannabinoids, including CBD and THC.